Development and validation of an HPLC-UV method for analysis of methylphenidate hydrochloride and loxapine succinate in an activated carbon disposal system - Pooja Bakshi; Andrew Korey; William Fowler; Ajay K. Banga (Elsevier, 2018)
Unused medications have the possibility of being abused, causing serious harm to individuals who were not prescribed the drug. The Food and Drug Administration (FDA) recommends the proper disposal of unused prescribed medications to maintain safety and prevent environmental hazards. However, many of the current disposal techniques do not properly address safety. A drug disposal pouch containing granular activated carbon offers a unique disposal method to deactivate residual or expired medication in a convenient, effective, and safe manner. A robust and validated method for methylphenidate hydrochloride and loxapine succinate was developed using high-performance liquid chromatography (HPLC) and the deactivation efficiency of the disposal system was tested. Methylphenidate hydrochloride was analyzed on a C18 analytical column (250 mm × 4.60 mm, 100Å) using acetonitrile-water (0.05% (v/v) trifluoroacetic acid) as the mobile phase at a flow rate of 1.0 mL/min with a run time of 15 min and retention time of 7.8 min. Loxapine succinate was separated on a C8 100Å (250 mm × 4.6 mm, 5 µm) column maintained at 25 °C using a flow rate of 1.0 mL/min. The run time was 10 min and the retention time of the drug was around 4.6 min. Mobile phase was composed of acetonitrile and water (0.3% triethylamine) at pH 3.0 as 40:60 (v/v). Reference standard solutions (100 µg/mL) for both drugs were prepared by dissolving in mobile phases. These methods provide good linearity (R2 = 0.999) over the range of 5-100 µg/mL for methylphenidate hydrochloride and 0.1-100 µg/mL for loxapine succinate. The assay methods were successfully applied to study the deactivation of these drugs. Keywords: Methylphenidate hydrochloride, Loxapine succinate, Activated carbon, Analytical method development, FDA drug disposal